2017
DOI: 10.1186/s13567-017-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and virulence characterization of highly prevalent Streptococcus agalactiae circulated in bovine dairy herds

Abstract: Bovine mastitis caused by Streptococcus agalactiae continues to be one of the major veterinary and economic issues in certain areas of the world. The more prevalent S. agalactiae strains that cause bovine mastitis in China dairy farms belong to a number of bovine-adapted sequence types (STs) ST67, ST103 and ST568. However, it is unknown why these STs can emerge as highly prevalent clones in bovine dairy farms. Here, to determine if a variety of virulence characteristics were associated with these highly preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 51 publications
3
50
0
Order By: Relevance
“…In this case, in most cases, the etiology of mastitis is multifactorial and the disease always arises on the background of a decrease in immunobiological protection, both at the local and system level, and is accompanied by changes in immune reactivity (Hamilton et al, 2006;Wu et al, 2015). However, the microbial factor is of paramount importance in the application of the pathogenetic mechanisms of this pathology, and therefore knowledge and determination of the biological balance between microorganisms and microorganisms is a significant moment in improving the methods of diagnosis, prevention and treatment of cows Pang et al, 2017).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In this case, in most cases, the etiology of mastitis is multifactorial and the disease always arises on the background of a decrease in immunobiological protection, both at the local and system level, and is accompanied by changes in immune reactivity (Hamilton et al, 2006;Wu et al, 2015). However, the microbial factor is of paramount importance in the application of the pathogenetic mechanisms of this pathology, and therefore knowledge and determination of the biological balance between microorganisms and microorganisms is a significant moment in improving the methods of diagnosis, prevention and treatment of cows Pang et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…Despite this, the researchers constantly encountered problems in interpreting the results (Singh et al, 2011;Wang et al, 2014;Al-Farha et al, 2017;Sato et al, 2017). It was related to the of dynamic changes in the quantitative composition of somatic cells in different periods of lactation, daily oscillations in their numbers; study species and individual peculiarities of animals (Zhelavskyi, 2005;Kurjogi et al, 2014;Lombardini et al, 2017;Pang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Immunobiological protection of the body is provided by a system of organs, tissues and cells that interact with pathogenic factors: bacteria, viruses, mycoplasmas, rickettsiae, fungi, parasites and ensure their destruction and elimination from the body. At the same time, the immune system carries out censorship control in the body recognizes and neutralizes moused, invaded, apoptotic cells and cells with signs of oncogenic transformation (Vernay et al, 2012;Tizard, 2013;Kurjogi & Kaliwal, 2014;Pang et al, 2017;Ruegg, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic diversity and clonal relatedness of S. agalactiae strains recovered from human and animal infections have been previously demonstrated by pulsed-field gel electrophoresis (PFGE) (Pinto et al 2013). Studies performed in different countries showed capsular types Ia, II, III, IV and V predominant in human and bovine infections, including Brazil (Pinto et al 2013;Carvalho-Castro et al 2017;Pang et al 2017).…”
Section: Introductionmentioning
confidence: 99%